The Spectrum of Manifestations of Severe Acute Respiratory Syndrome-Coronavirus 2 (SARS-CoV2) Infection in Children: What We Can Learn From Multisystem Inflammatory Syndrome in Children (MIS-C) - Panaro, Salvatore; Cattalini, Marco (Frontiers in Medicine, 2021)
Multisystem Inflammatory Syndrome in Children (MIS-C) is defined as a clinically serious condition requiring hospitalization with fever, multi-system organ disfunction, inflammatory biomarkers increase. The syndrome develops in the context of a probable or ascertained Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV2) infection, but other possible aetiologies should be ruled out for definitive diagnosis. On the clinical side, along with the multi-system involvement, myocarditis with heart failure and shock is the most striking feature. Capillary leak is another fundamental feature of MIS-C. In fact, shock and hemodynamic compromise in MIS-C can occur also in the absence of laboratory evidence of myocardial inflammation, with preserved cardiac function and rapid reversibility. Since the first observations of MIS-C patients, it was evident that there is a delay between the peak of adult cases of Coronavirus disease 19 (COVID-19) and the MIS-C peak. Moreover, SARS-Cov2 isolation in children with MIS-C is not always possible, due to low viral load, while positive serology is far more commonly observed. These observations lead to the interpretation of MIS-C as a post-infectious disease. Although the exact pathogenesis of MIS-C is far from being elucidated, it is clear that it is a hyperinflammatory disease with a different inflammatory response as compared to what is seen in acute SARS-CoV-2 infection and that the disease shares some, but not all, immunological features with Macrophage Activation Syndrome (MAS), Kawasaki Disease (KD), Hemophagocytic Lymphohistiocytosis (HLH), and Toxic Shock Syndrome (TSS). Different mechanisms have been hypothesized as being responsible, from molecular mimicry to antibody dependent enhancement (ADE). Some evidence has also been collected on the immunological profile of patients with MIS-C and their difference from COVID19.